Using “ways of thinking and practising” to analyse final year medical student reflections and underlying concepts in preparedness for practice - Leyland, Rachel; Neve, Hilary; Drake, Elizabeth; Collett, Tracey (Frontiers in Medicine, 2025)
IntroductionEnsuring that medical students are prepared for future practice is challenging for all medical schools. Most studies of preparedness involve newly qualified doctors and use quantitative methods such as self-report surveys focused on defined competencies, and often find graduates are unprepared for the complex and challenging areas of real-world practice. Qualitative methods, using conceptual ideas linked to learning such as ‘Ways of Thinking and Practising’ (WTP) are little explored in this area but could offer rich and useful insights about graduates’ preparedness. WTP recognises that, in addition to specific knowledge and skills, students need to understand the complex links between theory and practice and what it means to be part of their disciplinary community, in terms of culture, values and ways of seeing and being in the world. This study explored the written reflections of final year medical students on the threshold of practice, as they looked back at reflections from their previous years of study. It aimed to identify disciplinary WTP described by students and gain insights into their developing grasp of these.MethodsThirty six reflections were analysed and a thematic analysis undertaken, using WTP as a sensitising concept.ResultsSix inter-related WTP were identified. Illustrative quotes are provided which demonstrate how grasping each WTP involved students making connections between different elements of their learning and the ‘what’, ‘how’ and ‘why’ of knowing. Students reflected on the factors that facilitated their learning. Two resulting ‘changes in self’ were identified: a sense of confidence and self-efficacy, and a feeling of readiness for responsibility.DiscussionGrasping the WTPs identified may be a helpful part of preparing for practice, and understanding what facilitates this may be of use in informing future curricular design.